Modeling of micro-annulus propagation along cementing interface in stimulated horizontal wellbore. Issue 5 (2nd November 2021) - Yan, Yan; Guan, Zhichuan; Yan, Weijun
ABSTRACT: Once there are micro-annulus at cementing interfaces in the process of reservoir stimulation, it is easy to form fluid channeling in the later development. Fluid channeling reduces the efficiency of reservoir development and even the service life of oil and gas wells. Based on the characteristics of 'multi-stage' in stimulated reservoir volume, a mathematical model was set up to calculate the interface debonding length driven by hydraulic pressure. The propagation process of micro-annulus in stimulated reservoir volume was also analyzed. The results show that the propagation speed of the micro-annulus gradually slows down with the progress of fracturing. Meanwhile, the debonding azimuth of the micro-annulus and the cement elastic modulus have dominant effects on the propagation length. It is recommended that the setting position of the packer be outranged from the debonding area of the cementing interface in the design of the stimulated reservoir volume scheme to avoid fluid channeling between the stages. This study can predict the unsealing length of cement sheath during hydraulic fracturing as a reference for the optimization of fracturing parameters.